The neutral gas in the environs of the Wolf Rayet stars in the Circinus OB1 association - Giacani, Elsa Beatriz (2004)
We have investigated the neutral hydrogen in the direction of the Circinus OB1 association with particular emphasis in the study of the vicinity of the WR stars WR 65 and WR 67. The HI line data were obtained with the Australia Telescope Compact Array with a synthesized beam of 4. 00 × 2. 07 and a velocity resolution of 1.1 km s−1. These data led to the discovery of a large cavity surrounded by an almost complete shell in agreement with the locations and distances of the two WR stars. We propose that the HI features constitute an interstellar bubble created by the powerful winds of the WR stars and their progenitors. By assuming a distance of 3 kpc, we calculate for this HI bubble a linear radius of 22 pc, a swept-up mass of 1600 M and an expansion velocity of more than 7 km s−1. High angular resolution IRAS infrared data (HIRES) reveal the presence of a ring with good spatial correlation with the HI shell. Eight IRAS protostellar candidates located around the HI cavity suggest that star formation may be taking place in the shell. Further investigation is required to confirm this proposition.